Potential Mechanisms of Metformin-Induced Apoptosis in HeLa Cells - Zhaoli Chu; Yao Tan; Chenxing Xu; Dongting Zhangsun; Xiaopeng Zhu (Biomolecules, 2023)
Metformin is a traditional antidiabetic drug that also shows potential antitumor effects in cervical cancer. However, some of its apoptosis-related mechanisms are still unclear. In this study, flow cytometry, western blotting, and RNA sequencing (RNA-seq) were used to evaluate the molecular mechanisms of metformin in HeLa cells. The results showed that metformin inhibited cell viability and promoted apoptosis, the protein expression level of Caspase-3 (CASP3) was increased and that of BCL-2 was decreased in HeLa cells treated with metformin. The RNA-seq results indicated a total of 239 differentially expressed genes between the metformin and control check (CK) groups, with 136 genes upregulated and 103 genes downregulated, and 14 of them were found to be associated with apoptosis signaling pathways. The DDIT3 and HRK genes were robustly upregulated in HeLa cells by the endoplasmic reticulum (ER) stress and the mitochondrial pathway of apoptosis. Metformin also affects the expression of PPP2R5C, PPP2R5A, and RRAGA, which participate in biological processes such as PI3K-AKT, mTOR, and AMPK signaling pathways. Metformin mediates the expression of related genes to induce apoptosis.